Fenomena Pengemis Lansia Di Banda Aceh - Vanisha, Shara (JAROW: Journal of Ar-Raniry on Social Work, 2024)
The phenomenon of someone becoming an elderly beggar raises the question of what motives are behind the decision to become a beggar. Motive can be said to be an impulse within humans to act, to fulfill their life needs and as a force within humans which causes them to act or act to fulfill their needs or achieve certain goals. This research aims to analyze the phenomenon of elderly beggars, the factors that influence becoming beggars, and determine the efforts made by the government to address the phenomenon of elderly beggars in Banda Aceh. The object of this research is elderly beggars as people who carry out begging or begging activities in Banda Aceh City. This research uses qualitative research methods with data collection techniques in the form of observation, interviews, documentation and literature study. The results of the research show that the phenomenon of elderly beggars in Banda Aceh City uses certain strategies to attract the attention of donors, including: a) using symbols of poverty, b) using religious symbols and narratives, c) bringing small merchandise. The factors behind someone preferring to be a beggar are: 1) limited job opportunities, 2) not having special skills, 3) not wanting to try and preferring instant things. The efforts made by the government are a collaboration between the Banda Aceh City Social Service, the Islamic Sharia Service, Satpol PP and wilayatul Hisbah (WH) to arrest and empower elderly beggars.